Social Media Sentiment Analysis: Public Opinion on Yogyakarta Tourism - Wulan Purnama Sari; Nadia Ayu Rahma Lestari; Atwar Bajari; Hanny Hafiar; Puji Lestari (Fakultas Usluhuddin dan Dakwah UIN Syekh Wasil Kediri, 2026)
Social media has become an essential influence in the digital era, as it is today. Various parties, ranging from individuals and institutions, have accounts for multiple purposes. Thus, measuring social media use is essential for assessing its success, including in the tourism sector. Tourism in the digital era uses social media to shape public opinion and attract tourists. On that basis, this study aims to explain and analyze the results of measuring social media sentiment on public opinion of Yogyakarta tourism. The concept of public opinion is used in the study to measure the views of the digital community regarding tourism in Yogyakarta, one of Indonesia’s leading tourist destinations. This study was conducted using a quantitative approach using Brand24 to measure social media sentiment. The results of the study show that sentiment on social media is neutral, indicating that information related to Yogyakarta tourism is objective, with the most reach on TikTok.